2019
DOI: 10.1103/physrevd.100.035035
|View full text |Cite
|
Sign up to set email alerts
|

Addendum to “Impact of polarization observables and Bcτν on new physics explanations of the b

Abstract: In this addendum to Ref. [1], we update our results to include the recent measurement of RðDÞ and RðD Ã Þ by the Belle Collaboration [2]: RðDÞ Belle ¼ 0.307 AE 0.037 AE 0.016 and RðD Ã Þ Belle ¼ 0.283 AE 0.018 AE 0.014, resulting in the new HFLAV fit result RðDÞ ¼ 0.340 AE 0.027 AE 0.013, RðD Ã Þ ¼ 0.295 AE 0.011 AE 0.008, exhibiting a 3.1σ tension with the Standard Model. We present the new fit results and update all figures, including the relevant new collider constraints. The updated prediction for RðΛ c Þ … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
107
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 120 publications
(111 citation statements)
references
References 27 publications
4
107
0
Order By: Relevance
“…the new Belle measurements, see Refs. [33][34][35][36][37]) 1 . On the other hand, particular NP scenarios such as: charged scalars [46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62], leptoquarks (both scalar and vector) , extra gauge bosons [47,94,[98][99][100][101][102][103][104][105][106][107][108][109][110][111], right-handed neutrinos [62,[106][107][108][109][110][111][112][113], R-parity violating (RPV) supersymmetric couplings [31,[114][115]…”
Section: Introductionmentioning
confidence: 99%
“…the new Belle measurements, see Refs. [33][34][35][36][37]) 1 . On the other hand, particular NP scenarios such as: charged scalars [46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62], leptoquarks (both scalar and vector) , extra gauge bosons [47,94,[98][99][100][101][102][103][104][105][106][107][108][109][110][111], right-handed neutrinos [62,[106][107][108][109][110][111][112][113], R-parity violating (RPV) supersymmetric couplings [31,[114][115]…”
Section: Introductionmentioning
confidence: 99%
“…that can be measured by LHCb and will provide an experimental consistency check of the anomaly. The current prediction reads [39] R(Λ c ) = R SM (Λ c )(1.15 ± 0.04) = 0.38 ± 0.01 ± 0.01 .…”
Section: The R(d ( * ) ) Anomalymentioning
confidence: 96%
“…While the latter has not been measured directly, upper bounds of 30% [60] and even 10% [61] have been put forward in the literature. A recent critical reassessment however showed that even values as large as 60% cannot be excluded at present [38,39].…”
Section: The R(d ( * ) ) Anomalymentioning
confidence: 97%
See 1 more Smart Citation
“…To find the constrain on |y L 33 |, we utilize the 1D global fit value of Ref. [22] [11,24]. A detailed study with all three y R 12 (or y R 13 ), y R 23 , y L 23 non-vanishing couplings would be interesting in the light of new flavor and direct search results.…”
Section: Constraints On Leptoquark Yukawa Couplingsmentioning
confidence: 99%